Online Behavior and the Transformation of Interpersonal Communication in the Social Media Era - Rifaldi Datu; Djerlin Felisa Antara; Jevelin Januarsi Sumangando; Hestifari Rintawati Kakunsi; Ariel Edward Handoko; Julio Rivaldo Patroli (Syntax Corporation Indonesia, 2025)
The widespread use of social media has changed the way people communicate with each other, especially among young adults, especially university students. This study aims to explore online behavior and the transformation of interpersonal communication among Indonesian university students in the social media era. Questionnaires were administered to 125 university students to collect data on their online behavior, communication patterns, and relationships. The results showed that university students in Indonesia spend an average of 3-4 hours per day on social media, and most of them use social media to communicate with family and friends. The study also found that social media has changed interpersonal communication among university students, with most of them preferring to communicate online rather than in person. The implications of this study are discussed, and recommendations are made for future research.